Environmental impacts of a local circular economy business model : a carbon and water footprint analysis for smartphone refurbishment - Zumegen, Anna (2020)
Climate change is creating harm for the environment and humanity. Companies contribute significantly to global warming and environmental destruction. Hence, to prevent the climate crisis, the traditional linear economy has been transformed. The circular economy is a way to create a sustainable economy by decreasing the environmental impacts of companies like GHG emissions, resource usage, and environmental destruction. (Bocken et al., 2016). The growing ICT sector is an important actor in this area, particularly through the rapidly increasing amounts of WEEE, the rising GWP, and the increasing usage of resources. The inappropriate treatment of the toxic and harmful WEEE represents a growing problem (European Commission, 2020b), which can be decreased through smartphone refurbishment. This thesis discusses the benefits and drawbacks of smartphone refurbishment as a circular economy strategy with a special focus on the analysis of carbon and water footprints. The carbon footprint and water footprint calculations are done comprehensively for the case company ASW from Belgium, which works as an optimized example. The calculations are also done for less optimized refurbishment scenarios. The findings of the thesis suggest that smartphone refurbishment is environmentally beneficial over smartphone production. The carbon footprint of smartphone refurbishment (6.3922 – 24.22 kgCO2e/device) is significantly lower for every calculated scenario compared to the CF of a newly manufactured smartphone (83.83 kgCO2e/device). Similar, the WF of all scenarios (1161.54 – 2946.71 L/device) is significantly lower than the WF of smartphone production (12075.46 L/device). Furthermore, the refurbishment has the potential to decrease resource usage signifcantly. The thesis suggest that development and improvement of the infrastructure of smartphone refurbishment will lead to further decreased environmental impacts. Next to this, the thesis points out the research gap on the water usage in the ICT sector.